Domestic Abuse and Elder Abuse in Wales: A Tale of Two Initiatives. (25th July 2018) - Wydall, Sarah; Clarke, Alan; Williams, John; Zerk, Rebecca
Abstract: The abuse of older people in domestic settings is both a public health problem and a human rights issue. In 2013, the Welsh government used its new legislative powers and embarked upon two initiatives in the areas of adult safeguarding and domestic abuse, leading to the introduction of two pieces of primary legislation. The first was the Social Services and Well-being (Wales) Act 2014, which placed safeguarding 'adults at risk' on a statutory basis and imposed new duties on local authorities. The second was the Violence against Women, Domestic Abuse and Sexual Violence (Wales) Act 2015, which addressed how public-sector bodies responded to domestic abuse and introduced a more strategic approach. Using research based in Wales, this article discusses the extent to which the two pieces of legislation promote a collaborative and integrated response from adult safeguarding and domestic abuse services and highlights some implications for practice. More strategic alignment between the two acts will create an environment within which older victim-survivors of domestic abuse have equal access to justice options and support services as their younger counterparts.